To solve you should write this as an equation. X+2=3+2x. Add -2x to each side to get all the x's in one place, and this gives you -2x+x+2=3. Subtract the number two from each side to get all the numbers on the right and the variables on the left which gives you -2x+x=3-2. Simplify by adding one x to the -2x which leaves -1x, and then by subtracting 3 from 2 leaving 1. Your equation is now -1x=1, so therefore x=-1 because -1*-1=1. You can check your work by plugging in -1 for the x's: -1+2=3+2*-1. -1+2=1 and 2*-1=-2+3=1, 1=1 is a true statement, tada!